Individuals, householders, citizens : Malayalis and family planning, 1930-1970 - Devika, J. (Zubaan, 2008)
The creation of widespread public consent for family planning in Kerala, which ensured the non-coercive implementation of birth control in Malayali society, has been regarded as no less than the jewel in the crown of the Kerala Model of social development. Individuals, Householders, Citizens reconstructs the history of the generation of such assent to produce a critical examination of this crucial aspect of social development in Kerala. It participates in the ongoing feminist critique of the Kerala Model, seeking to unravel the particular ways in which people were interpellated into the discourse of Family Planning. Devika s study adds to the new inter-disciplinary work on questions traditionally considered native to demography. It employs some of the insights of economists and demographers on Kerala s demographic transition as entry points for critical historical inquiry into questions of gender and power in contemporary Kerala. The book is of interest to anyone interested in Kerala s experience of social development and its demographic achievements .